Floristics of road forestry conflicting with the electrical networks: a case study in the southern region of Minas Gerais State - de Oliveira, Altamir Fernandes; Neves, Cinara Liberia Pereira; Pereira, Gabriel de Assis; Garcia, Fernando Henrique Silva; Coelho, Silvério José; Pereira, Jose Aldo Alves (Ornamental Horticulture, 2018)
Urban afforestation produces a great enhancement in the flora of cities, but if improperly implanted they generate disturbances, especially if the implanted species are not adapted to electric energy networks The objective of this paper was to carry out a qualitative-quantitative survey on urban afforestation through the interconnection with the electricity network in the five cities with most issues of electricity shutdown caused by trees in the South of Minas Gerais state At the end of the inventory there were 221 individuals belonging to 58 species, 56% of which were exotic and 44% native. Eight species counted for 51.99% of the total inventory, being: Jacaranda mimosifolia, Platanus acerifolia, Murraya paniculata, Lagerstroemia indica, Schinus molle, Ficus benjamina, Bauhinia variegata and Poincianella pluviosa. Only the species Schinus molle and Poincianella pluviosa are native. More than half of the inventoried trees presented a size incompatible with the electrical network, species of large (55.59%), medium (24.42%) and small (19.99%) sizes, to be implanted for urban afforestation. The selected streets had narrow widths, but the sidewalks had ideal widths for the implantation of afforestation. Treetop pruning was performed in 20% of the individuals evaluated, a practice that is widely used due to the presence of large species. The species evaluated in the inventory showed height ranging from 2 to 6 meters, not reaching their maximum potential when belonging to medium and large species. For the studied cities it is recommended a new evaluation of the urban afforestation, seeking to identify the appropriate patterns to the urban environment.